(untitled) (European Journal of Economics, Finance and Business Development, 2024)
This article highlights the importance of project management plan development and time planning in public private partnership projects. The project management plan is the main document that defines the detailed organization and execution of the project. This document describes each stage of the project from acceptance to its implementation. The plan defines the strategies, tasks, deadlines, and success criteria used in managing the project. Time planning defines project deadlines, order of execution, critical deadlines and interdependencies. The abstract describes the role of project management plan development and scheduling in public-private partnership projects to ensure efficient and effective project execution. This article shows how the project management process is structured, managed, and critical to success.